2002
DOI: 10.4161/cc.1.6.258
|View full text |Cite
|
Sign up to set email alerts
|

Cell Cycle Phase-Specific CHemotherapy: Computation Methods for Guiding Treatment

Abstract: Computational models of cancer chemotherapy enhance the understanding of in vitro, in vivo, and clinical trial data and have the potential to contribute to the design of rational treatment regimens. In particular, mechanistic, predictive models are superior to statistical, phenomenological descriptions of data. Mechanistic models based on functional data from tumor biopsies will enable the response to treatment to be predicted for a specific patient, in contrast to statistical models in which the probability o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(21 citation statements)
references
References 48 publications
0
21
0
Order By: Relevance
“…Other authors designed specific models of the anticancer therapy (13,14), some theoretical, others oriented to fit data, and some including a modelization of cell proliferation through the cell cycle.…”
Section: Discussionmentioning
confidence: 99%
“…Other authors designed specific models of the anticancer therapy (13,14), some theoretical, others oriented to fit data, and some including a modelization of cell proliferation through the cell cycle.…”
Section: Discussionmentioning
confidence: 99%
“…only when the cell is in a (set) of specific phases of its cycle [5]. Moreover, the distribution of phases over a given population of tumor cells is unlikely to be uniform, that is to say, the phase-in-the-cycle is an individual component of each cell's current state description.…”
Section: Introductionmentioning
confidence: 99%
“…an efficiency greater than the additive ones), by targeting different processes in the cell cycle, see [12]. The evolution of the cell cycle-mediated drug resistance, or kinetics resistance, has been addressed by means of mathematical and computational models, summarized in [5], employed also for control-based therapeutic design, see [14], [9]. While some therapy agents are able to kill a cell during all the phases of its cycle, cell-cycle specific agents are efficient This work was not supported by any organization M. Alamir and M. Fiacchini are with CNRS, Gipsa-lab, Control System Department, University of Grenoble Alpes.…”
Section: Introductionmentioning
confidence: 99%
“…A number of reports have also suggested that cell cycle control points, such as the G 1 /S and G 2 /M transitions, are potential targets for chemoprevention and cancer treatment in humans (3)(4)(5).…”
Section: Introductionmentioning
confidence: 99%